Determination of Total Polyphenol Content in Bali Local Red Pomegranate (Punica granatum L.) Peel Extract Using UV-Vis Spectrophotometry - Kumara Dewi, Ni Wayan Rika; Mahardika, Ida Bagus Putra; Swari Santi, Made Dwike; Ugrasena, Putu Yudha (Poltekkes Kemenkes Denpasar, 2025)
ABSTRACTPomegranate (Punica granatum L.) peel is a major agro-industrial byproduct rich in bioactive compounds, particularly polyphenols, which have attracted increasing interest for functional food and phytopharmaceutical applications. However, studies specifically analyzing the total polyphenol content of the local Balinese red pomegranate peel are still limited. This study aimed to determine the total polyphenol content and perform phytochemical screening of the red pomegranate peel collected from Bali, Indonesia. The research employed an experimental laboratory design. Red pomegranate peels were collected from Jadi Village, Tabanan Regency, Bali. The peels were dried, powdered, and extracted by maceration using 96% ethanol. Phytochemical screening was performed to detect major secondary metabolites. The total polyphenol content was determined using the Folin-Ciocalteu method with gallic acid as the standard, measured by UV-Vis spectrophotometry at 765 nm. All analyses were conducted in triplicate. The extraction yielded 25.78% of viscous ethanol extract. Phytochemical screening confirmed the presence of flavonoids, tannins, saponins, and steroids/triterpenoids. The standard gallic acid calibration curve showed good linearity with a correlation coefficient (R²) of 0.9916. The total polyphenol content was found to be 147.953 mg GAE/g at 1,000 ppm concentration and 34.136 mg GAE/g at 100 ppm. The findings demonstrate that the local Balinese red pomegranate peel contains significant polyphenolic compounds and secondary metabolites with antioxidant potential. This supports its potential for valorization as a source of natural antioxidants for functional food, nutraceutical, or sustainable packaging applications. Further studies are recommended to assess its antioxidant activity and to compare seasonal and varietal variations.Keywords: Punica granatum L.; polyphenol content; Folin-Ciocalteu; UV-Vis spectrophotometry; phytochemical screening.ABSTRAKKulit delima (Punica granatum L.) adalah produk sampingan agro-industri utama yang kaya akan senyawa bioaktif, terutama polifenol, yang semakin menarik minat untuk aplikasi makanan fungsional dan fitofarmasi. Namun, studi yang secara khusus menganalisis total kandungan polifenol dari kulit buah delima merah Bali lokal masih terbatas. Studi ini bertujuan untuk menentukan kandungan total polifenol dan melakukan skrining fitokimia pada kulit buah delima merah yang dikumpulkan dari Bali, Indonesia. Penelitian ini menggunakan desain laboratorium eksperimental. Kulit delima merah dikumpulkan dari Desa Jadi, Kabupaten Tabanan, Bali. Kulit buah delima dikeringkan, dihaluskan, dan diekstraksi dengan cara perendaman menggunakan etanol 96%. Skrining fitokimia dilakukan untuk mendeteksi metabolit sekunder utama. Kandungan total polifenol ditentukan menggunakan metode Folin-Ciocalteu dengan asam galat sebagai standar, diukur dengan spektrofotometri UV-Vis pada 765 nm. Semua analisis dilakukan dalam triplikat. Ekstraksi menghasilkan 25,78% ekstrak etanol kental. Skrining fitokimia mengkonfirmasi keberadaan flavonoid, tanin, saponin, dan steroid/triterpenoid. Kurva kalibrasi asam galat standar menunjukkan linearitas yang baik dengan koefisien korelasi (R²) sebesar 0,9916. Kandungan total polifenol ditemukan sebesar 147,953 mg GAE/g pada konsentrasi 1.000 ppm dan 34,136 mg GAE/g pada 100 ppm. Temuan tersebut menunjukkan bahwa kulit delima merah Bali lokal mengandung senyawa polifenolik yang signifikan dan metabolit sekunder dengan potensi antioksidan. Ini mendukung potensinya untuk valorizasi sebagai sumber antioksidan alami untuk makanan fungsional, nutraceutical, atau aplikasi kemasan berkelanjutan. Studi lebih lanjut direkomendasikan untuk menilai aktivitas antioksidannya dan membandingkan variasi musiman serta varietas. Kata kunci:Punica granatum L.; kandungan polifenol; Folin-Ciocalteu; spektrofotometri UV-Vis; skrining fitokimia.